2022
DOI: 10.1177/08862605221092074
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying Victimization and Associated Factors Among School-Aged Adolescents in China

Abstract: There has been a significant amount of research on correlates of bullying victimization, but most prior studies are descriptive and do not distinguish between different types of bullying. The current study used a case-control study design to explore factors related to different types of bullying victimization, including physical, relational, verbal, sexual, property, and poly-bullying victimization. This study was conducted in a southern city in China, including 3054 cases who self-reported being victims of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Rural adolescents lacking close parental supervision and protection were more vulnerable to bullying victimization due in part to their lack of self-esteem, sense of security, or unhealthy lifestyles [66,[79][80][81]. Furthermore, the current study indicated that rural adolescents living in a nuclear family and not boarding at school experienced a higher risk of poly-bullying victimization than their urban counterparts, which to some extent was not surprising because poly-bullying victimization was associated with paternal problematic behaviors such as excessive alcohol consumption [82]. Previous literature also indicated that rural parents were more likely to have mental disorders and problematic behaviors, and even abuse their children [22,83,84].…”
Section: Discussionmentioning
confidence: 50%
“…Rural adolescents lacking close parental supervision and protection were more vulnerable to bullying victimization due in part to their lack of self-esteem, sense of security, or unhealthy lifestyles [66,[79][80][81]. Furthermore, the current study indicated that rural adolescents living in a nuclear family and not boarding at school experienced a higher risk of poly-bullying victimization than their urban counterparts, which to some extent was not surprising because poly-bullying victimization was associated with paternal problematic behaviors such as excessive alcohol consumption [82]. Previous literature also indicated that rural parents were more likely to have mental disorders and problematic behaviors, and even abuse their children [22,83,84].…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have found that physical bullying victimization is associated with family domains (i.e., parenting style). In contrast, relational and verbal bullying victimization is associated with multiple social domains (e.g., not being an only child, poor relationships with classmates) [89]. Future research can provide a more detailed analysis of different types of bullying victimization and explore whether different types have distinct predictive factors.…”
Section: Limitations and Suggestions For Future Studiesmentioning
confidence: 99%